Collective Flourishing and Community Well-being: A Conceptual Paper - Abraham Perumbrayil Francis (Space and Culture, India)
We coexist in an interdependent world where all are connected, and every action has both visible and silent ripples. We are in a world of change, and if there is one thing we can say for sure, it is the highly disruptive age with moving goalposts, more so regarding uncertainty. This disruption has caused significant damage to our families, relationships, jobs, communities, and economy, as well as political discourses or intercultural/ international relations, thereby affecting the health of individual people and safety, severely affecting the well-being of individuals besides societies. These are indeed challenging times. However, this situation also presents an opportunity for transformational breakthroughs and the birth of new paradigms that can help us better deal with societal issues. So, how does one become someone who flourishes regardless of what life throws one’s way? How can we foster a culture of care, compassion, and hope in our communities? What does it take to unite our communities and build their resilience despite external threats or opportunities? Well, as scientific evidence suggests, humans can flourish. Thus emerges the fundamental question of what stops us from moving forward.  This paper is based on critical reflection, a literature review, and extensive practice experiences of working in the community sector, which has provided the impetus to find an alternative lens to look at the challenges of the current technologically advanced, fast-paced society.